2006
DOI: 10.1136/adc.2006.097246
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of watching TV during venipuncture

Abstract: Aims: To assess the analgesic effect of passive or active distraction during venipuncture in children. Methods: We studied 69 children aged 7-12 years undergoing venipuncture. The children were randomly divided into three groups: a control group (C) without any distraction procedure, a group (M) in which mothers performed active distraction, and a TV group (TV) in which passive distraction (a TV cartoon) was used. Both mothers and children scored pain after the procedure. Results: Main pain levels rated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 22 publications
(13 reference statements)
2
50
0
6
Order By: Relevance
“…Our study showed that watching cartoon video influenced children"s pain perception and distress at initiation, at five minutes and at termination of administration of Intravenous injection with the use of the Oucher scale, and found that TV watching (ie watching an age appropriate cartoon on TV) was more effective than active distraction performed by their mothers. 16 The result of present study showed that cartoon distraction therapy is effective in reducing pain in children during painful medical procedure. Which are consistent with previous investigationsby Rockville, MD (1992) that distraction and adult coaching appear to be beneficial for young children undergoing painful medical procedures.…”
Section: Discussionmentioning
confidence: 70%
“…Our study showed that watching cartoon video influenced children"s pain perception and distress at initiation, at five minutes and at termination of administration of Intravenous injection with the use of the Oucher scale, and found that TV watching (ie watching an age appropriate cartoon on TV) was more effective than active distraction performed by their mothers. 16 The result of present study showed that cartoon distraction therapy is effective in reducing pain in children during painful medical procedure. Which are consistent with previous investigationsby Rockville, MD (1992) that distraction and adult coaching appear to be beneficial for young children undergoing painful medical procedures.…”
Section: Discussionmentioning
confidence: 70%
“…72 Interestingly, there is experimental evidence that television viewing can have an analgesic effect in 7-to 12-year-old children undergoing venipuncture. 73 Given the novelty and potential importance of the soothability finding, we conducted a post hoc analysis (data not presented) to further probe the soothability effect in girls. Results indicated that standardized weight increased in both low-and high-soothability girls in a monotonic and parallel fashion until the age of 4 years, but then diverged between 4 and 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…The visual distraction would reduce suffering and, at the same time, allow venipuncture to be performed in an emergency. The distraction diverts the stressful stimulus, and centering thepatient on a pleasant stimulus [28]. The present study aims to investigate the efficacy of three interventions (Buzzy, distracting cards and balloon inflating) on mitigating pain and anxiety associated with venipuncture in a group of pediatric patients.…”
Section: Introductionmentioning
confidence: 99%